Principal component analysis of the Serological response to Plasmodium Falciparum using a Multiplex bead-based assay in Nigeria - Jonathan S. Schultz; Mary Okoli; Scott Lee; Colleen M. Leonard; Dean Sayre; Charles M. Heilig; Perpetua Uhomoibhi; Abiodun Ogunniyi; Nnaemeka Ndodo; Nwando Mba; Ado G. Abubakar; Oluwaseun Akinmulero; et al. (Scientific Reports)
Abstract Characterization of serological responses to Plasmodium falciparum (Pf) is of interest to understand disease burden and transmission dynamics; however, their interpretation is challenging. Dried blood spots from 30,815 participants aged 6 months to 15 years from the 2018 Nigeria HIV/AIDS Indicator and Impact Survey were analyzed by multiplex bead-based assay to measure immunoglobulin G (IgG) to Pf-stage-specific MSP-1, AMA-1, GLURPR0, LSA-1, and CSP. These IgG levels were analyzed by principal component analysis (PCA). PC1 and PC2 scores explained 41% and 17% of the total variance, respectively. PC1 unit vectors represented seropositivity. PC2 unit vectors for blood-stage antigens were in opposite directions to liver-stage and sporozoite antigens. PC2 scores were correlated with MSP-1 positively (R = 0.52, P < 0.001) and CSP negatively (R=-0.65, P < 0.001) and may help identify areas with prior exposure but higher risk for increased infections or epidemics. PCA of Pf serology can provide summary scores to possibly inform future programmatic interventions.